Co-substrate strategy for improved power production and chlorophenol degradation in a microbial fuel cell. (26th July 2019) - Yu, Yang; Ndayisenga, Fabrice; Yu, Zhisen; Zhao, Mingyue; Lay, Chyi-How; Zhou, Dandan
Abstract: A co-substrate strategy has the potential to contribute toward minimizing the poisoning of refractories on the anode respiring bacteria (ARB), which is a necessity for microbial fuel cell (MFC) to recover energy from toxic wastewater. However, little is known about the underlying mechanisms. This study employed 4-chlorophenol (4-CP) as target refractory pollutant and acetate as co-substrate. The co-substrate could stimulate 4-CP sensitive extracellular electron transfer (EET) enzymes' activity under 4-CP stress, such as succinate dehydrogenase (complex II) and cytochromes c OmcA and OmcB. For the microbial community, ARB were still abundant during 4-CP toxification; Azospirillum and Dechloromonas were enriched to conduct aromatic ring breakage and dechlorination. Thus, a 4.3-fold increased power generation was achieved, and the 4-CP and chemical oxygen demand (COD) removals increased by ∼42% and ∼53%, respectively. An easy-to-degrade substrate could improve power re-coverage from refractory wastewater by enhancing EET enzyme activity and optimizing the microbial community. Graphical abstract: Image 1 Highlights: Co-substrate strategy was applied to recover energy from refractories via a MFC. Both power generation and chlorophenol removal were promoted by the co-substrate. Co-substrate contributes enhanced the activation of EET pathway enzymes. With co-substrate, 4-CP degrading genera were enriched and ARB cells could survive.